FAST TRIMARAN PASSENGER SHIPS FOR THE ARCHIPELAGO REGIONS - Wolter R Hetharia (ALE Proceeding, 2021)
This paper deals with the design process of passenger trimaran ships provided to be operated in the archipelago regions. This specific ship and area are defined due to the need of transport passenger in the archipelago region. The problems of worse sea conditions, low passenger rate, safety, the need of fast passenger transport are solved with the existence of fast passenger trimaran. Several tasks were executed with the objective is to find design specification of the trimaran ships. The ships were designed based on the standart procedure in ship design. The input design, design process, design considerations and other requirements and rules were applied during design process. Two small trimaran multi-function were designed and built to be operated as fishing boat and restricted passenger transport. Meanwhile, two passenger trimarans were designed with the concepts of â€œwave piercing trimaranâ€ and Small Waterplane Area-Wider Deck (SWA-WD) for the main hull form. The results of the task were proving the blue-print design. In, addition, one task is still condicting for design of Patrol Trimaran Boat. The results of those designs are presented in the paper including the design specifications and documents for each kind of trimaran ships. In conclusion, the design specifications are prepared for future ship construction. It is recommded that some ship design parameters should be confirmed before the construction stage.